PERMANÊNCIA DE EGRESSOS DA PÓS-GRADUAÇÃO EM EDUCAÇÃO STRICTO SENSU NA REGIÃO CENTRO-OESTE ENTRE 2009 E 2019 - Felipe Vieira Gimenez (2022)
This study is part of the line of research on the History, Policies, and Education of the Postgraduate Program in Education at the Federal University of Mato Grosso do Sul (FAED/UFMS). The object of this research is the permanence of graduates of stricto sensu master's and doctoral postgraduate programs at UFMS, UFGD, UFMT, UFG, and UnB, universities placed in the Brazilian Midwest region. The research aims to analyze the determinants of permanence according to the answers of graduates from stricto sensu postgraduate studies (master's and doctorate) in Education in the Brazilian Midwest Region. The research hypothesis is that the offer of scholarships in master's and doctorate stricto sensu programs in Education –although it is justified as a policy to encourage the training of human resources for the country- is characterized as a strategy for permanence and completion of the stricto sensu postgraduate program by grant holders. The study covered the period between the years 2009 and 2019. The work included data analysis from bibliographic and documental research and a semi-structured survey. The procedures adopted for data collection consisted of a literature review stage on the topic and concepts used in the study, followed by procedures and application of a questionnaire to graduates and heads of postgraduate studies on Education in the Midwest region. Historical-dialectical materialism is the theoretical framework that supports this research. It leads to articulations and analysis of categories such as contradiction, totality, mediation, reproduction, and hegemony in order to understand the transformations in higher education in the context of postgraduate studies, considering educational, social, political, and economic aspects. As a result of the data analysis, there were identified three main categories for the permanence of graduate students in postgraduate programs in Education in addition to the scholarships: 1) personal determinants; 2) social relationships; 3) institutional reasons. Based on the dialectical perspective, it was identified that the permanence of graduate students in postgraduate education programs in the Midwest region is materialized through institutional actions that interfere with this process, which is multidetermined for geopolitical, economic, cultural, personal, and social class issues. Keywords: Postgraduate studies; Permanence; Graduate students; Midwest Brazil.